Assessment of Ngonu Area – Bamenda Division – Cameroons Province, 2. Re-assessment of (1924-1930) (Colonial Letters and the Contact of Knowledges, 1924)
This file contains colonial memoranda and re-assessment report including maps on Ngonu, Bamenda
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies